Role Playing with Digital Comics in Preventing Bullying and Cyberbullying Behavior in Elementary School - Dina laili oktaviana; Rusnilawati (Jurnal Ilmiah Sekolah Dasar, 2022)
Education is a process that makes a humane benchmark for educators and devotees to achieve common educational goals. The process proceeds in a specific environment and uses a variety of actions. Lack of attention of teachers in the use of various methods and models to prevent bullying. This study aims to analyses the differences in student attitudes and students’ knowledge about the impact of bullying before and after applying role playing models with digital comic media. The participants of this study were 12 teachers. The method used was quantitative method with experiments. The sample taken was 20 four grader students in elementary school. The data collection method used in this study were observation pretests and post tests, and questionnaire. The data analyses ued in this study were normality test, homogeneity test, knowledge hypothesis test, and attitude hypothesis test. The results of the research showed that there was a significant influence of the use of role playing model and digital comic media in preventing bullying behavior in elementary school. This implementation allows teachers to use a model with media to attract students’ attention so that they can understand the lesson in the learning process easily.